The Role of Financial Distress in Moderating the Relationship Between Financial Leverage and Key Management Compensation in Consumer Cyclical Sector - Utomo, Ginaris Prio; Maulana, Afandi Ukik Wahyu Bintang; Sridadi, Ahmad Rizki (e-Journal Ekonomi Bisnis dan Akuntansi, 2025)
This research investigates the effect of financial leverage on the compensation of top executives and how financial distress mediates this relationship. A quantitative method with multiple and moderated regression analyses was applied to test the hypothesis using the data of 24 consumer cyclical companies listed in the Indonesia Stock Exchange from 2018 to 2022. The results indicate that financial leverage significantly and positively influences the key management compensation, and thus, the higher levels of debt leads to higher compensation for managers. The results also show that financial distress significantly moderates this relation, which negatively affects the linkage of executive compensations and leverage. This moderation suggests that in financial distress, firms might cut down on management compensation as a response to the increased risks associated with high leverage. These findings contribute valuable insights into capital structure and compensation strategies, especially in different financial contexts, and provide practical recommendations for corporate leaders in designing executive pay.